2007
DOI: 10.4049/jimmunol.179.7.4335
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phosphorylation of CD5 in Chronic Lymphocytic Leukemia B Cells and Analysis of CD5-Regulated Genes in a B Cell Line Suggest a Role for CD5 in Malignant Phenotype

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 68 publications
1
51
1
Order By: Relevance
“…There is also evidence to suggest that CD5 is involved in promoting survival. Natural phosphorylation of regulatory tyrosines on CD5 in CLL B cells reflects chronic activation (18), and sustained signaling through the BCR promotes further expression of CD5 (37). Thus, BCR engagement favors the expression of CD5 (38) which provides viability signals for B cells in a subset of CLL patients (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence to suggest that CD5 is involved in promoting survival. Natural phosphorylation of regulatory tyrosines on CD5 in CLL B cells reflects chronic activation (18), and sustained signaling through the BCR promotes further expression of CD5 (37). Thus, BCR engagement favors the expression of CD5 (38) which provides viability signals for B cells in a subset of CLL patients (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…These cells contain transcripts for CD5-E1B but not for CD5-E1A (6,16). Daudi B cells, which are negative for surface CD5 but transfected with cd5-E1A to induce membrane CD5 expression of CD5, were supplied by Prof. A. Dalloul (University of Nancy, Nancy, France) (17,18). Jurkat T cells and COS-1 cells were purchased from the American Type Culture Collection.…”
Section: Cell Preparationmentioning
confidence: 99%
“…Another interesting observation was reported by Richardson et al [36] who identified an enhanced expression of CCR7 on ZAP70(+) B-CLL cells, leading to an increased responsiveness of CCR7 to its ligands CCL19 and CCL21. Gary-Gouy et al [61] found that CD5 phosphorylation may lead to an additional expression increase of CCR7 on B-CLL cells. Furthermore, Ticcioni et al [56] found that CCL19 and CCL21 contribute to prolonged survival of B-CLL cells by activating ERK1/2 and Akt.…”
Section: Ccl19 Ccl21 and Their Common Receptor Ccr7mentioning
confidence: 99%
“…Although it is predominantly expressed on naïve T lymphocytes, CCR7 is also detectable on B lymphocytes (on which it was initially identified) [1,58,59]. CCR7 also has been demonstrated to have a great impact on the development of secondary lymphoid organs [60,61]. Till et al [60] demonstrated that due to increased CCR7 expression on B-CLL cells and CCL19 and CCL21 expression in high endothelial venules, TEM was significantly higher for malignant B cells of patients with LN involvement compared to those without this organomegaly.…”
Section: Ccl19 Ccl21 and Their Common Receptor Ccr7mentioning
confidence: 99%
“…It is known that malignant cells from CLL are undergoing a process of continuous stimulation due to CD5 activation and cell survival. (Gary-Gouy et al, 2007) A continuous activation of an antiapoptotic pathway explains the CLL cells survival. Apolipoprotein E4-very low density lipoproteins is responsible for the high level of apoptosis in CLL cells.…”
Section: Cholesterol Metabolism Disordermentioning
confidence: 99%